Influence of Media on Seasonal Influenza Epidemic Curves. (September 2016) - Saito, Satoshi; Saito, Norihiro; Itoga, Masamichi; Ozaki, Hiromi; Kimura, Toshiyuki; Okamura, Yuji; Murakami, Hiroshi; Kayaba, Hiroyuki
Highlights: The period from the onset to peak of seasonal influenza epidemic curve correlated positively with the search volume index calculated using Google trends search in pre-epidemic season. The steepness of the epidemic curve and the total dose of anti-flu drug prescriptions of the season inversely correlated with the volume of media information on influenza in pre-epidemic period. Education through media was suggested to have an effect on the vaccine coverage, steepness of the epidemic curve and the scale of seasonal influenza epidemics. Education through media may contribute to infection prevention by improving vaccine coverage and other self-protective manners. Abstract: Back ground: Theoretical investigations predicting the epidemic curves of seasonal influenza have been demonstrated so far; however, there is little empirical research using ever accumulated epidemic curves. The effects of vaccine coverage and information distribution on influenza epidemics were evaluated. Materials and Methods: Four indices for epidemics (i.e., onset-peak duration, onset-end duration, ratio of the onset-peak duration to onset-end duration and steepness of epidemic curves) were defined, and the correlations between these indices and anti-flu drug prescription dose, vaccine coverage, the volume of media and search trend on influenza through internet were analyzed. Epidemiological data on seasonal influenza epidemics from 2002/2003 to 2013/2014 excluding 2009/2010 season were collected from National Institute of Infectious Diseases of Japan. Results: The onset-peak duration and its ratio to onset-end duration correlated inversely with the volume of anti-flu drug prescription. Onset-peak duration correlated positively with media information volume on influenza. The steepness of the epidemic curve, and anti-flu drug prescription dose inversely correlated with the volume of media information. Pre-epidemic search trend and media volume on influenza correlated with the vaccine coverage in the season. Vaccine coverage had no strong effect on epidemic curve. Conclusion: Education through media has an effect on the epidemic curve of seasonal influenza.